Ontology for mapping of data classes for improved data exchange on cotton production in Brazil. (10th April 2015) - Junior, Clovis dos Santos; Hirakawa, Andre Riyuiti
The research put forth in this paper has multidisciplinary characteristics focusing on cotton fibre production and computational solutions to improved data exchange in this segment. The study is divided into three parts, the identification of the cotton fibre production processes, the formal ontology for identifying the data classes and finally the proposal of a specific metadata standard for cotton fibre production. The research's focus is the used data exchange in the cotton culture. The absence of a specific standard for this segment favours the heterogeneity in the various data sources, making it difficult or impossible to cross or merge data to generate reliable and useful information. The contribution of the research lies in improving the information exchange used in agricultural systems in the cotton fibre production.